2020
DOI: 10.1111/joim.13182
|View full text |Cite
|
Sign up to set email alerts
|

A follow‐up survey of patients with acquired angioedema due to C1‐inhibitor deficiency

Abstract: A follow-up survey of patients with acquired angioedema due to C1-inhibitor deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…10/13 patients had the C1‐INH‐AAE diagnosis established within 1 year after the first UAE, which correlates with the diagnostic window in literature 42 . However, it could be observed that patients who experienced UAE had a C1‐INH‐AAE diagnosis earlier 43 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…10/13 patients had the C1‐INH‐AAE diagnosis established within 1 year after the first UAE, which correlates with the diagnostic window in literature 42 . However, it could be observed that patients who experienced UAE had a C1‐INH‐AAE diagnosis earlier 43 …”
Section: Discussionmentioning
confidence: 79%
“…42 However, it could be observed that patients who experienced UAE had a C1-INH-AAE diagnosis earlier. 43 In case of bradykinin-mediated angioedemas, establishing an early diagnosis is fundamental, as UAE has a crucial role in both hereditary and acquired AEs, being the only edema localization that can be lethal without proper treatment.…”
Section: Incidence Of Uae In Case Of Hereditary Angioedema Patients With Normal C1-inh Levelsmentioning
confidence: 99%
“…The upper-respiratory airway oedema is a potentially life-threatening condition due to asphyxiation. In this type of angioedema, the swelling is bradykinin mediated and attributed to excessive consumption of the C1-INH or inhibition of C1-INH function by autoantibodies (2,4). In most cases, the excessive use of the C1-INH is caused by lymphoproliferative tissue (1)(2)(3), in the context of either malignant conditions, especially NHL (2,5), or benign ones, like monoclonal gammopathy of uncertain significance (2,6).…”
Section: Discussionmentioning
confidence: 99%
“…Acquired angioedema (AAE) due to C1-inhibitor (C1-INH) deficiency (C1-INH-AAE) is a very rare disorder that usually appears in patients with lymphoproliferative and/or autoimmune diseases due to excessive activation of the classical complement pathway leading to depletion of C1-INH (1)(2)(3). Clinically, C1-INH-AEE manifests with recurrent episodes of nonpruritic, nonpitting angioedema without urticaria which last two to four days and can involve any part of the body (4). As the symptoms of C1-INH-AAE can pre-cede a diagnosis of lymphoproliferative disease with months or years and confers an increased risk for developing non-Hodgkin lymphoma, the early diagnosis is very important (2).…”
Section: Introductionmentioning
confidence: 99%
“…Differences include onset at later age, underlying diseases such as lymphoma or benign monoclonal gammopathy (MGUS), occasional constitutional symptoms (B symptoms), and often decreased C1q levels. 39 , 44 , 77 , 78 C1q level should be measured to investigate patients for AAE-C1-INH, especially those with new onset of angioedema after the age of 30 years and a negative family history. C1q is nearly always normal in HAE.…”
Section: The Differential Diagnosis Of Haementioning
confidence: 99%